Diagnóstico de salud bucodental y factores de riesgo en los centros educativos primarios: Primero de Junio, Julia Jaramillo, 10 de Diciembre y secundarios Colegio Nacional Agustín Curipoma de la parroquia Gualel del cantón Loja año 2013. - Ambuludí Hualpa, Tatiana Lucía (2013)
Dental caries and periodontal disease are considered, the most prevalent oral diseases around the world, for that reason is necessary to identify the risk factors, the causality of these and their relation with these pathologies . Risk factors associated with these oral diseases, constitute a measurable probability and they have predictive value in its preventing, these pathologies are considered the main causes of teeth loss. The objectives of this research work were, diagnose the oral pathologies present, its prevalence and risk factors associated with them, in the students of the following schools: Primero de Junio, Julia Jaramillo, 10 de Diciembre and the National High School “Agustin Curipoma”, of the Gualel parish, year 2013. We designed a quantitative, descriptive and prospective research study. The research study area encompassed the 100% of the population into the four Educational Institutions mentioned above; it was constituted for 129 students. Oral examination was performed to each patient, with respect to the diagnostic of dental caries and gingival inflammation, malocclusions and dental alterations. Data were recorded in the medical dental history. We realized a survey with closed questions about oral hygiene, eating habits and oral care. Caries experience was measured by CPOD and CEO indices, which describe respectively, the prevalence of caries in permanent and temporary dentition in a person, through the number of carious teeth, sealed teeth and missing teeth or indicated extraction for reason of caries. To determine alterations in gingival level, we analyzed the presence of spontaneous bleeding, recession and we applied the Simplified Oral Hygiene Index (IHOS) it is necessary to determine the grade of a person's oral hygiene. Processed and analyzed the collected data, the results show that: the oral health of this population is affected due to several indicators that involved in a negative form in the oral health, for lack of education about oral care, of promotion and prevention oral health, little interest and ignorance of the population about the importance of oral cleanliness. The most prevalent oral pathologies are: dental caries appearing in 79.8% of the total population, gingival inflammation in 41.1%, and presence of malocclusion in 57.2%. TRADUCCION: Dra. Rosario Veintimilla A.